2003
DOI: 10.1074/jbc.m301420200
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive GABAA Receptor Endocytosis Is Dynamin-mediated and Dependent on a Dileucine AP2 Adaptin-binding Motif within the β2 Subunit of the Receptor

Abstract: Receptor endocytosis is an important mechanism for regulating the synaptic efficacy of neurotransmitters. There is strong evidence that GABA A receptor endocytosis is clathrin-dependent; however, this process is not well understood. Here we demonstrate that in HEK 293 cells, endocytosis of GABA A receptors composed of either ␣ 1 ␤ 2 ␥ 2 L or ␣ 1 ␤ 2 subunits is blocked by the dominant negative dynamin construct K44A. Furthermore, we identify a dileucine AP2 adaptin-binding motif within the receptor ␤ 2 subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 31 publications
4
87
1
Order By: Relevance
“…The ␤-AR in the G i -coupled state can activate Src kinase, and subsequently the GTPase dynamin, which is known to play a role in the budding of vesicles from the plasma membrane during internalization (21,22). In addition, it has been shown that the ␤-AR can activate Src kinase in a G protein-independent manner (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The ␤-AR in the G i -coupled state can activate Src kinase, and subsequently the GTPase dynamin, which is known to play a role in the budding of vesicles from the plasma membrane during internalization (21,22). In addition, it has been shown that the ␤-AR can activate Src kinase in a G protein-independent manner (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…2c) representing residues 401-412 to bind 2 (see below), we conclude that we have identified a previously uncharacterized atypical binding motif (between ␤-subunit residues 401 and 410) for the AP2 complex, which is conserved within the ICDs of all GABA A R ␤ subunits. Recently a dileucine motif (LL) in the intracellular domain of the ␤2 subunit (residues 344 and 345) has been suggested to be of significance in regulating GABA A R internalization via a clathrin-dependent mechanism, and this motif is also found in the ICDs of the ␤1 and ␤3 subunits (31). However, the direct binding of LL motifs to the 2 subunit of the AP2 complex is controversial (17)(18)(19).…”
Section: Identification Of An Atypical 2 Binding Motif In Gabaar ␤ Sumentioning
confidence: 99%
“…GABA A Rs undergo clathrin-mediated endocytosis and can be detected in endocytic structures (1,8,10,11,27). HAP1 has been localized to clathrin-coated vesicles and the endocytic pathway (23)(24)(25)(26) and has been implicated in endocytic protein trafficking (26), suggesting that HAP1 may be involved in the endocytic sorting of GABA A Rs.…”
Section: Hap1mentioning
confidence: 99%
“…Modifications of GABA A R cell surface number underlie changes in inhibitory postsynaptic current amplitude, providing an effective mechanism for regulating the efficacy of synaptic inhibition (3)(4)(5)(6)(7)(8)(9)(10). Under basal conditions, synaptic GABA A Rs are undergoing clathrin-dependent endocytosis (8,10,11). Given this constitutive endocytosis, the cellular fate of internalized GABA A receptors is critical as their recycling or degradation will affect the number of receptors on the cell surface, and hence the efficacy of synaptic inhibition.…”
mentioning
confidence: 99%